2011
DOI: 10.1007/s13105-011-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short- and long-term strength exercise on cardiac oxidative stress and performance in rat

Abstract: Increase in heart metabolism during severe exercise facilitates production of ROS and result in oxidative stress. Due to shortage of information, the effect of chronic strength exercise on oxidative stress and contractile function of the heart was assessed to explore the threshold for oxidative stress in this kind of exercise training. Male Wistar rats (80) were divided into two test groups exercised 1 and 3 months and two control groups without exercise. Strength exercise was carried by wearing a Canvas Jacke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Recent studies reported that recurring high dose AAS administration and physical training in mice produce significant increase in HW. (8,36) Both groups had significantly higher HW/BW ratio than control and non significantly higher than exercise-trained group. Riezzo et al (27) observed that exogenous AAS administration induced cardiac hypertrophy in vitro and in vivo, and when combined with exercise, these steroids change exercise-induced physiological cardiac hypertrophy to pathophysiological cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies reported that recurring high dose AAS administration and physical training in mice produce significant increase in HW. (8,36) Both groups had significantly higher HW/BW ratio than control and non significantly higher than exercise-trained group. Riezzo et al (27) observed that exogenous AAS administration induced cardiac hypertrophy in vitro and in vivo, and when combined with exercise, these steroids change exercise-induced physiological cardiac hypertrophy to pathophysiological cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 86%
“…(SOD). In contrast, Ahmadiasl et al [24] found no improvement in the antioxidant capacity of rats subjected to jumping protocol after 4 and 12 weeks of training at rest. However, there was no increase in oxidative parameters after acute exercise, showing that this type of training ameliorates the deleterious effects of acute exercise in relation to oxidative stress.…”
Section: Some Authors Have Observed That the Rt Promoted Adaptation Imentioning
confidence: 90%
“…showing lower levels of lipid peroxidation [22] and increased activity of superoxide dismutase and catalase enzyme in erythrocytes [21]. In animals, the existing studies verified the effect of the RT in skeletal muscle [23], cardiac [24] and liver [18]. Murlasits et al [23] have reported that RT three times a week promotes a 66% increase in the expression of the enzyme superoxide dismutase DOI: 10.4236/oalib.1104411 2 Open Access Library Journal M. Costa-Junior et al…”
Section: Some Authors Have Observed That the Rt Promoted Adaptation Imentioning
confidence: 96%
See 1 more Smart Citation
“…A HSD is a major cause of hypertension, and it accelerates the secondary aging process and can lead to premature death (Samadian et al, 2016). Long-term exercise results in a number of physiological adaptations such as an increase angiogenesis and antioxidant ability that improves muscle performance and enhances the resistance of the muscle to fatigue (Ahmadiasl et al, 2012;Petersen and Greene, 2008). However, a HSD can impair skeletal muscle performance by inhibiting its angiogenesis and increasing oxidative stress (Bernardi et al, 2012;Lenda and Boegehold, 2002;Li et al, 2018;Petersen and Greene, 2008).…”
Section: Introductionmentioning
confidence: 99%